The impact of economic and non-economic determinants on circular economy in Vietnam: A perspective of sustainable supply chain management - Chau, Ka Yin; Hong, Manh Pham; Lin, Chen-Hsien; Ngo, Thanh Quang; Phan, Thi Thu Hien; Huy, Pham Quang (Technological and Economic Development of Economy, 2023)
The projections of UN indicate that by the year 2030, natural resource demand will become threefold as of today. This for sure surpasses existing capacity due to which many countries are facing depletion issue or might face depletion issue in coming years. Realizing this challenge, economies all over the globe are shifting towards circular economy development in order to address the environmental sustainability issue. In Vietnam, economic activities are normally based on the principle of linear economy. However, this traditional approach not only creates shortage of natural resources but also becomes the reason of environmental destruction. Thus, the study is an attempt to find out the harmonious relationship of economic and non-economic determinants with circular economy in the presence of sustainable supply chain management as a moderator. By employing structural equation modelling, findings indicate that circular economy is the right direction as it ensures job security and bring quality education and political stability. Results also confirm that sustainable supply chain management increases the strength of positive relationship of said variables. In the light of the evidences, the paper proposes few suggestions and implications to promote the development of circular economy so that economic growth and environmental quality can be achieved at the same time.